Pengaruh Perceived Social Support terhadap Psychological Well-Being Mahasiswa yang sedang Menyusun Skripsi - Azka Khoirunnisa; Dewi Rosiana (UNISBA Press, 2023)
Abstract. This study aims to determine the effect of perceived social support on psychological well-being in students who are preparing a thesis at Bandung Islamic University. The study used a quantitative approach with the causality method and used simple random sampling. The research subjects were male and female students who were preparing a thesis at the Islamic University of Bandung totaling 247 people, with ages from 21 to 25 years. Data analysis using simple linear regression analysis and descriptive statistical analysis. Data collection was carried out using the Multidimensional Scale of Perceived Social Support (MSPPS) measuring instrument from Zimet (1988) adapted by Laksmita et al., (2020) for perceived social support variables and using the Ryff Scale of Psychological Well-Being which was adapted by Rachmayani and Ramdhani (2014) for psychological well-being variables. The results of data analysis state that there is a positive linear relationship and a significant influence between perceived social support on psychological well-being with a contribution value of 30.7% and with a significant value of 0.00 < from alpha of 0.05. This means that the higher the perceived social support that is useful and positive for students, the more significant it will be in improving their psychological well-being. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh perceived social support terhadap psychological well-being pada mahasiswa yang sedang menyusun skripsi di Universitas Islam Bandung. Penelitian menggunakan pendekatan kuantitatif dengan metode kausalitas dan menggunakan simple random sampling. Subjek penelitian adalah mahasiswa laki-laki dan perempuan yang sedang menyusun skripsi di Universitas Islam Bandung yang berjumlah 247 orang, dengan usia dari 21 sampai 25 tahun. Analisis data menggunakan analisis regresi linear sederhana dan analisis statistic deskriptif. Pengumpulan data dilakukan menggunakan alat ukur Multidimensional Scale of Perceived Social Support (MSPPS) dari Zimet (1988) yang diadaptasi oleh Laksmita et al., (2020) untuk variabel perceived social support dan menggunakan Ryff Scale of Psychological Well-Being yang telah diadaptasi oleh Rachmayani dan Ramdhani (2014) untuk variabel psychological well-being. Hasil analisis data menyatakan adanya hubungan linear yang positif dan pengaruh signifikan antara perceived social support terhadap psychological well-being dengan nilai kontribusi sebesar 30,7% dan dengan nilai signifikan.0,00 < dari alpha sebesar 0,05. Artinya, semakin tinggi dukungan sosial yang dirasakan yang berguna dan positif pada mahasiswa maka secara signifikan akan berpengaruh meningkatkan psychological well-being nya.